Anorectal Gastrointestinal Stromal Tumour: A Case Treated with Radical Surgery - Joshi, Arbin (Journal of Nepal Health Research Council, 2018)
Gastrointestinal Stromal Tumour involving rectum and anal canal is an extremely rare entity. This is a case report of a 47 years lady presented with fresh rectal bleed associated with rectal pain and foul smelling rectal mucus discharge. On rectal examination, she had a firm mass palpable about 1.5 cm from anal verge. Considering the size of the tumour and its close proximity with cervix and involvement of levator muscles, extralevator abdominal perineal excision of rectum was undertaken with good recovery after surgery. It was followed by imatinib therapy.